Prominent Naturally Derived Oxidative-Stress-Targeting Drugs and Their Applications in Cancer Treatment - Eunsun Lee; Dongki Yang; Jeong Hee Hong (Antioxidants)
The relationship between oxidative stress and cancer has been extensively studied and highlighted, along with its role in various aspects of angiogenesis. The modulation of oxidative levels and the adaptive mechanisms of oxidative stress in cancer systems are attractive research themes for developing anti-cancer strategies. Reactive oxygen species (ROS) are involved in various pathophysiological processes and play crucial roles in DNA damage and angiogenesis. Although cancer cells have developed various adaptive defense mechanisms against oxidative stress, excessive ROS production has been proposed as an anti-cancer strategy to induce cellular apoptosis. In particular, natural-source-based antioxidants have been identified as effective against cancers, and various delivery platforms have been developed to enhance their efficacy. In this review, we highlighted the anti-cancer components (plumbagin, quercetin, resveratrol, curcumin, xanthatin, carvacrol, telmisartan, and sulforaphane) that modulate ROS levels and the recent targeting platforms used to increase the application of anti-cancer drugs and the developed delivery platforms with diverse mechanisms of action. Further, we summarized the actual doses used and the effects of these drug candidates in various cancer systems. Overall, this review provides beneficial research themes for expanding cancer-targeting fields and addressing limited applications in diverse cancer types.